2021
DOI: 10.3390/ijerph18041911
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Self-Report Instruments for the Measurement of Anxiety in Hospitalized Children with Cancer

Abstract: Anxiety has been identified as one of the most severe and long-lasting symptoms experienced by hospitalized children with cancer. Self-reports are especially important for documenting emotional and abstract concepts, such as anxiety. Children may not always be able to communicate their symptoms due to language difficulties, a lack of developmental language skills, or the severity of their illness. Instruments with sufficient psychometric quality and pictorial support may address this communication challenge. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 55 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…The questionnaire captured data regarding sociodemographics, the adolescents’ schooling, and social distancing in relation to COVID-19. The Numerical Rating Scale (range 0-10) (NRS) was also used to assess anxiety [22] . This study probed two additional questions, the first being the open question: Feel free to comment about your thoughts on vaccination against COVID-19, on which the qualitative data was based.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire captured data regarding sociodemographics, the adolescents’ schooling, and social distancing in relation to COVID-19. The Numerical Rating Scale (range 0-10) (NRS) was also used to assess anxiety [22] . This study probed two additional questions, the first being the open question: Feel free to comment about your thoughts on vaccination against COVID-19, on which the qualitative data was based.…”
Section: Methodsmentioning
confidence: 99%
“…33 The development of the PicPecc tool follows established guidelines 34 and was based on the theoretical framework of person-centred care, 4 on published systematic reviews 9 and on systematic reviews conducted within the project on assessment tools for nausea, 35 and anxiety. 36 Children with cancer, their legal guardians and healthcare professionals have been involved throughout the development process. The study protocol outlined here pertains to the evaluation and implementation phases.…”
Section: Methods and Analysis Study Designmentioning
confidence: 99%
“…However, the use of the RCMAS-2 is not restricted only to educational contexts since it has also been used in the clinical field (Mahakwe et al, 2021). In a group of 370 children with cancer, Wuet al (2016) found adequate reliability levels with exception of the Physiological anxiety factor (α = .65).…”
Section: Propiedades Psicométricas De La Escala De Ansiedad Manifiesta En Niños Revisada Segunda Edición En Estudiantes Peruanosmentioning
confidence: 99%